The predictive role of autonomous-related self of adolescent and the critical thinking disposition of parents on adolescent psychological resilience - Ermiş, Ece Naz; YILDIRIM, MELİS SERAY ÖZDEN (My University, 2017)
The aim of this study is to determine the predictive role of autonomous-related self of adolescent and the critical thinking disposition of parents on adolescent psychological resilience. The study was carried out on 339 participants who were selected randomly including 113 adolescents (in the range of 14-18 ages; female 57, male 56) and 113 mother – 113 father of these adolescents. Adolescent Psychological Resilience Scale, Autonomous-Related Self Scale, Critical Thinking Disposition Scale and Demographical information form were used for data collection. Pearson Correlation, Independent Samples t-Test and Hierarchical Regression were used in analysis of data. The findings reveal that there was a statistically significant positive correlation between adolescent psychological resilience and critical thinking disposition of parents. Also there was a statistically significant positive correlation between adolescent psychological resilience and relatedness of adolescent. Furthermore there was a statistically significant positive correlation between family, peer and school support subdimensions of adolescent psychological resilience and relatedness. The results showed that there was no significant difference regarding to adolescent psychological resilience level according to gender. According to hierarchical regression analysis’ results there was a predictive role of relatedness subdimension of self-construal of adolescent and critical thinking disposition of parents on adolescent psychological resilience.
Keywords: Resilience; Autonomous-Related Self; critical thinking